2015
DOI: 10.1007/s40806-015-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

The Mask of Sanity Revisited: Psychopathic Traits and Affective Mimicry

Abstract: Three studies examined Jones' (Perspectives on Psychological Science, 9, 445-451, 2014) suggestion that psychopathic individuals use mimicry to avoid detection. In study 1, student, community, and offender participants posed fearful facial expressions while looking at a prototypical fear face. Expressions were coded for facial movements associated with fear and were rated on genuineness by a separate sample of undergraduates. Across samples, psychopathic traits were associated with increased use of typical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 63 publications
1
19
1
Order By: Relevance
“…He suggested that there is a degree of social mimicry necessary for appearing to be trustworthy, which increases the likelihood of interaction. To determine whether people who score higher on psychopathic traits are better at social mimicry, one study had samples of male students, community members, and inmates feign emotions that tend to be lacking in individuals with psychopathic traits, namely fear and remorse (Book et al 2016b). Posed fear expressions and feigned remorse stories were both judged as more genuine in individuals scoring higher on measures of psychopathy, including self-report measures and the Psychopathy Checklist Revised (PCL-R; Hare 2003), suggesting enhanced emotional mimicry.…”
Section: Social Mimicrymentioning
confidence: 99%
“…He suggested that there is a degree of social mimicry necessary for appearing to be trustworthy, which increases the likelihood of interaction. To determine whether people who score higher on psychopathic traits are better at social mimicry, one study had samples of male students, community members, and inmates feign emotions that tend to be lacking in individuals with psychopathic traits, namely fear and remorse (Book et al 2016b). Posed fear expressions and feigned remorse stories were both judged as more genuine in individuals scoring higher on measures of psychopathy, including self-report measures and the Psychopathy Checklist Revised (PCL-R; Hare 2003), suggesting enhanced emotional mimicry.…”
Section: Social Mimicrymentioning
confidence: 99%
“…Demetrioff suggests further research should examine individuals who solely score high on the trait of interpersonal manipulation and compare their judgment accuracy to those individuals high in other psychopathy facets. Book et al (2015) followed up their earlier work (Book et al, 2006) by examining the ability of individuals with psychopathic traits to mimic emotions, which would be consistent with the social predatory hypothesis. Three studies were completed.…”
Section: Victim Selectionmentioning
confidence: 86%
“…In the second study, undergraduate students completed the Psychopathic Personality Inventory and told a story about a time when they did something that they should have felt remorse for but didn't. Book et al (2015) found Factor 1 traits in psychopathy were positively related to genuineness scores. In the last study, four videos were shown to a sample of undergraduate students who rated false remorse stories told by violent offenders.…”
Section: Victim Selectionmentioning
confidence: 93%
“…Given that deception and manipulation are often dependent on one's ability to successfully interpret emotions in others, and display appropriate and authentic-looking emotional responses, we sought to reconcile how emotional processing deficits are manifested in the generation of emotional expressions in persons with high versus low levels of psychopathic traits. Past research suggests that psychopaths may not be as emotionally impaired as once suspected, and that they may display enhanced abilities to mimic emotion (i.e., fear) in order to successfully manipulate others (Book et al, 2015). That said, the study of how psychopathic individuals generate and display other primary emotions has been relatively neglected in past research, as well as whether they exhibit variations in expression as a function of veracity.…”
Section: Faking Faces: Psychopathic Traits and Feigned Emotional Exprmentioning
confidence: 99%
“…Of particular relevance to the present study, Book et al (2015) had nonclinical and forensic populations generate fearful facial expressions, which were later coded in terms of their facial action units. Their results indicated that those high in psychopathic traits were more successful at affective/emotional mimicry.…”
Section: Psychopathy and Emotional Expressionsmentioning
confidence: 99%